2022
DOI: 10.3389/fpsyg.2021.784858
|View full text |Cite
|
Sign up to set email alerts
|

Will This Help Be Helpful? Giving Aid to Strangers in the United States and Japan

Abstract: Japanese rank among the least likely to intervene to help a stranger in a non-emergency situation while Americans rank among the most likely. Across four studies, we demonstrate that Japanese are less likely to offer help to strangers because their decisions rely more heavily on the assessment of the needs of others. Accordingly, when there is uncertainty about the need for help, Japanese are less likely to intervene than Americans because without an understanding of the needs of recipient, the impact of inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
(43 reference statements)
1
0
0
Order By: Relevance
“…Similarly, the provider also expects a potentially negative evaluation from the support recipient and thus hesitates to provide support. This is consistent with the findings of Niiya et al (2022) , who also examined the provision of social support among Japanese people and found that it is highly dependent on the assessment of the needs of others. One could assume from these results that the “rejection avoidance” on both sides makes it difficult to support each other ( Hashimoto and Yamagishi, 2013 , 2016 ).…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, the provider also expects a potentially negative evaluation from the support recipient and thus hesitates to provide support. This is consistent with the findings of Niiya et al (2022) , who also examined the provision of social support among Japanese people and found that it is highly dependent on the assessment of the needs of others. One could assume from these results that the “rejection avoidance” on both sides makes it difficult to support each other ( Hashimoto and Yamagishi, 2013 , 2016 ).…”
Section: Discussionsupporting
confidence: 90%